Oxidative stress in bacteria (Pseudomonas putida) exposed to nanostructures of silicon carbide. (September 2015) - Borkowski, Andrzej; Szala, Mateusz; Kowalczyk, Paweł; Cłapa, Tomasz; Narożna, Dorota; Selwet, Marek
Abstract : Graphical abstract: Highlights: Silicon carbide nanostructures were produced by combustion synthesis. Oxidative stress in Pseudomonas putida was investigated. Peroxidase activity, expression of zwf-1 gene and cell viability were analyzed. SiC nanofibers and nanorods can induce oxidative stress in P. putida . Abstract: Silicon carbide (SiC) nanostructures produced by combustion synthesis can cause oxidative stress in the bacterium Pseudomonas putida . The results of this study showed that SiC nanostructures damaged the cell membrane, which can lead to oxidative stress in living cells and to the loss of cell viability. As a reference, micrometric SiC was also used, which did not exhibit toxicity toward cells. Oxidative stress was studied by analyzing the activity of peroxidases, and the expression of the glucose-6-phosphate dehydrogenase gene ( zwf1 ) using real-time PCR and northern blot techniques. Damage to nucleic acid was studied by isolating and hydrolyzing plasmids with the formamidopyrimidine [fapy]-DNA glycosylase (also known as 8-oxoguanine DNA glycosylase) (Fpg), which is able to detect damaged DNA. The level of viable microbial cells was investigated by propidium iodide and acridine orange staining.